Abdominal ectopic pregnancy. Issue 4 (4th July 2021) - George, Reshma; Powers, Edward; Gunby, Robert
Abstract: Abdominal pregnancy is a rare form of ectopic pregnancy with high morbidity and mortality. There are a limited number of case reports of abdominal ectopic pregnancies. We present a case of a 29-year-old woman who presented to her obstetrician at 17 weeks' gestation with abdominal pain. A sonogram and confirmatory magnetic resonance imaging demonstrated an abdominal ectopic pregnancy. The patient underwent exploratory laparotomy with removal of the ectopic pregnancy. Our case presents an opportunity to discuss a rare form of ectopic pregnancy and the importance of proper diagnosis and treatment to reduce morbidity and mortality.